Assessment of the effects of heat input on microstructure and mechanical properties in laser beam welded Haynes 188 undermatched joints - Odabasi, A.; Unlu, N.; Goller, G.; Kayali, E. S.; Eruslu, M. N. (Elsevier Science Sa, 2013)
CO2 laser butt-welding of Co-base superalloy Haynes 188 was performed on 2.1 mm-thick sheets with an average grain size of 21 mu m (ASTM #8). Nine different heat inputs in the range of 61.3-90.1 J mm(-1) were used. The corresponding solidification rates at the weld fusion zone were in the range of 2 x 10(3) to 1 x 10(4) degrees C s(-1). The distribution coefficients for the alloying elements in the laser beam welded samples were close to unity. The yield and tensile strengths, the strain hardening exponents, and the strength mismatch ratios decreased with increasing heat input. The corresponding joint efficiencies of the high and low heat input trials were 84% and 93%, respectively. Fractography analysis of the base material and laser beam welded sheets revealed dimple-like ductile fracture characteristics. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Cobalt based superalloy; Laser beam welding; Microstructure; Mechanical properties